Russia : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1999)
This paper reviews economic developments in the Russian Federation during 1990-98. Output fell precipitously in 1992-94 in response to the withdrawal of subsidies and the disruption in traditional economic relations, but the decline then began to taper off, and real GDP registered a small increase in 1997. However, the recovery proved short-lived, and GDP was already on a downward trend by the first half of 1998. This contraction was severely aggravated by the economic crisis that erupted in mid-1998.